Tomb and burials of the protestants as an question of state in the Empire Crisis (1869-1889) (Revista de História Regional, 2008)
In the ends of the decade of 1860, in the conjuncture of the incited disputes between regalism and ultramontanism, and of the intense campaign from the part of the political and intellectual elite in the defense of the protestant cause, the ecclesiastical hierarchy promoted a series of interdictions to the burial of the so called non-catholic in the public cemeteries of some localities, under the argument that they were addressed to the citizens of the Empire. These facts, showed clearly how limited and exclusive were the citizenship rights at that time. It is intended here, to identify the way death and dying were significant aspects through which, disputes around the enlargement of the citizen rights in the slavish and catholic Empire towards the protestant immigrants were expressed, in the context of the Empire Crisis.